Faktor-Faktor Yang Mempengaruhi Akuntabilitas Pengelolaan Dana Desa (Studi Kasus Desa Di Kecamatan Simeulue Barat) - Endra Gunawan; Jahrul Amin; Eliana E; Nurhayati N (Jurnal Ilmiah Mahasiswa Ekonomi dan Bisnis Islam, 2021)
This study aims to analyze the influence of leadership, transparency, use of information technology and internal control systems on the accountability of village village fund management in villages in West Simeulue District. The problem that arises is whether leadership, transparency in the use of information technology and internal control systems affect the accountability of village fund management in West Simeulue District? With a sample of 70 respondents and data obtained by distributing questionnaires to respondents. To test each item on each variable has been tested the validity and reliability of the instrument. The results show that simultaneously there is an influence between leadership, transparency, use of information technology, internal control systems and accountability of village fund management by 0.678 or 67.8% and 0.322 or 32.2% influenced by other variables. after the F test, the number Fcount > Ftable or (34,293>3.13) and a significant test that the p value of 0.000 <p is set at 0.05 which means it is significant. Partially shows that: 1. Leadership affects the accountability of village fund management Tcount 2.392> T table 1.667 and p value 0.020 < from p 0.05 means significant. 2. Transparency affects the accountability of village fund management Tcount 2,231 > Ttable 1,667 with p value 0.029 from <0.05 means significant. 3. The use of information technology affects the accountability of village fund management Tcount 1.953> Ttable 1.667 with p value 0.030 from <0.05 means significant. 4. The internal control system affects the accountability of village fund management Tcount 4.511> Ttable 1.667 with p value 0.000 from <0.05 means significant. This means that partially the influence of the internal control system on the accountability of village fund management is more dominant than leadership, transparency and the use of information technology.